The effect of EU 2006 sugar regime reform on vertical price transmission - Maurizio Aragrande; Mauro Bruni; Alberico Loi; Roberto Esposti (Agricultural and Food Economics, 2017)
CAP regulation of sugar sector has frequently been questioned because of its potential effect on competition. In 2006 the CAP reform of the sugar sector established a relevant break in policy trend with potential albeit untargeted effects on price transmission. In 2012 DG AGRI commissioned a study to assess the effects of the 2006 reform of the EU sugar regime on the price transmission within the sugar sector. This paper highlights the effects of the new CAP sugar regime on sugar retail price and on the degree of competition and concentration in the sugar industry. Vertical price transmission is tested through econometric models. The relationship between concentration and competition is analysed putting in relation the concentration index and a modified version of the Lerner index. Results of empirical investigation show that vertical price transmission asymmetries still exist after the reform, which in turn contributed to increase sugar sector concentration, partly confirming the validity of the Structure-Conduct-Performance assumptions. The sugar market is far from efficient and the reform only created more favourable conditions for its improvement.
Keywords: 330; Sugar reform; Vertical price transmission; EU